Establishing and characterising a new cell line from Calliphora vicina (diptera: calliphoridae) fly embryonic tissues - Ingred Pinillos; Cindy Pérez; Orlando Torres; Manuel A. Patarroyo; Felio J. Bello (Heliyon, 2022)
Insect cell lines represent a promising and expanding field as they have several research applications including biotechnology, virology, immunity, toxicology, cell signalling mechanisms and evolution. They constitute a powerful tool having a direct impact on human and veterinary medicine and agriculture. Although more than 1000 cell lines have currently been established from various insect species, Calliphora vicina-derived fly cell lines are lacking. This study was aimed at establishing a new C. vicina embryonic tissue-derived cell line. Adult flies were collected and embryonated eggs were mechanically homogenised and seeded in four types of culture media (L15, Grace's insect medium, Grace's/L15 and DMEM). Cell growth and morphological characteristics were recorded and cytogenetic and molecular patterns were determined. The CV-062020-PPB cell line was established and was shown to have optimal growth in Grace's/L15 medium. CV-062020-PPB cell monolayers that had been sub-cultured over 16 times consisted of firmly adhering cells having different morphologies; a fibroblast-like shape dominated and the karyotype had a 12-chromosome diploid number. RAPD-PCR analysis of the CV-062020-PPB cell line revealed a high similarity index and strong intraspecific relationship with C. vicina adult flies and a weaker relationship with the Lutzomyia longipalpis-derived cell line (Lulo). The CV-062020-PPB cell line constitutes the first cell line obtained from C. vicina embryonic tissues and represents an important basic and applied research tool.